The influence of menstrual cycle on bioimpedance vector patterns, performance, and flexibility in elite soccer players - Campa, F.; Micheli, M. L.; Pompignoli, M.; Cannataro, R.; Gulisano, M.; Toselli, S.; Greco, G.; Coratella, G. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To examine whether menstrual cycle affects body composition and bioimpedance vector analysis (BIVA) patterns, jumping and sprinting ability, and flexibility in elite soccer players.